Chemical structure of cichorinotoxin, a cyclic lipodepsipeptide that is produced by Pseudomonas cichorii and causes varnish spots on lettuce - Komatsu, Hidekazu; Shirakawa, Takashi; Uchiyama, Takeo; Hoshino, Tsutomu (Beilstein Journal of Organic Chemistry, 2019)
Pseudomonas cichorii, which causes varnish spots on lettuce and seriously damages lettuce production during the summer season in the highland areas of Japan (e.g., Nagano and Iwate prefectures) was isolated. The structure of a toxin produced by this organism was analyzed based on the detailed evaluation of its 2D NMR and FABMS spectra, and this compound has not been reported previously. We propose the name cichorinotoxin for this toxin. In conjunction with the D or L configurations of each amino acid, which were determined by Marfey’s method, we propose the structure of cichorinotoxin to be as follows: 3-hydroxydecanoyl-(Z)-dhThr1-D-Pro2-D-Ala3-D-Ala4-D-Ala5-D-Val6-D-Ala7-(Z)-dhThr8-Ala9-Val10-D-Ile11-Ser12-Ala13-Val14-Ala15-Val16-(Z)-dhThr17-D-alloThr18-Ala19-L-Dab20-Ser21-Val22, and an ester linkage is present between D-alloThr18 and Val22 (dhThr: 2-aminobut-2-enoic acid; Dab: 2,4-diaminobutanoic acid). Thus, the toxin is a lipodepsipeptide with 22 amino acids. The mono- and tetraacetate derivatives and two alkaline hydrolysates, compounds A and B, were prepared. We discuss here the structure–activity relationships between the derivatives and their necrotic activities toward lettuce.
Keywords: cichorinotoxin; lipodepsipeptide; necrotic lesion of lettuce; phytotoxin; Pseudomonas cichorii

(untitled) - Grogan, R. G.; Misaghi, I. J.; Kimble, K. A.; Greathead, A. S.; Ririe, D.; Bardin, R. (Phytopathology, 1977)

(untitled) - Kiba, A.; Lee, K. Y.; Ohnishi, K.; Park, P.; Nakayashiki, H.; Tosa, Y.; Mayama, S.; Hikichi, Y. (Physiol. Mol. Plant Pathol., 2009)

(untitled) - Kiba, A.; Sangawa, Y.; Ohnishi, K.; Yao, N.; Park, P.; Nakayashiki, H.; Tosa, Y.; Mayama, S.; Hikichi, Y. (Mol. Plant-Microbe Interact., 2006)

(untitled) - Pauwelyn, E.; Vanhouteghem, K.; Cottyn, B.; De Vos, P.; Maes, M.; Bleyaert, P.; Höfte, M. (J. Phytopathol., 2011)

Abstr. Ann. Meeting Phytopathol. Soc. Jpn. - Shirakawa, T.; Hoshino, T.; Uchiyama, T.; Ozaki, K. (Ann. Meeting Phytopathol. Soc. Jpn., 1992)

Abstr. Ann. Meeting Phytopathol. Soc. Jpn. - Shirakawa, T.; Ozaki, K. (Ann. Meeting Phytopathol. Soc. Jpn., 1994)

(untitled) - Takasugi, M.; Okinaka, S.; Katsui, N.; Masamune, T.; Shirata, A.; Ohuchi, M. (J. Chem. Soc., Chem. Commun., 1985)

(untitled) - Isogai, A.; Fukuchi, N.; Yamashita, S.; Suyama, K.; Suzuki, A. (Tetrahedron Lett., 1990)

(untitled) - Fukuchi, N.; Isogai, A.; Yamashita, S.; Suyama, K.; Takemoto, J. Y.; Suzuki, A. (Tetrahedron Lett., 1990)

(untitled) - Segre, A.; Bachmann, R. C.; Ballio, A.; Bossa, F.; Grgurina, I.; Iacobellis, N. S.; Marino, G.; Pucci, P.; Simmaco, M.; Takemoto, J. Y. (FEBS Lett., 1989)

(untitled) - Ballio, A.; Bossa, F.; Collina, A.; Gallo, M.; Iacobellis, N. S.; Paci, M.; Pucci, P.; Scaloni, A.; Segre, A.; Simmaco, M. (FEBS Lett., 1990)

(untitled) - Ballio, A.; Barra, D.; Bossa, F.; Collina, A.; Grgurina, I.; Marino, G.; Moneti, G.; Paci, M.; Pucci, P.; Segre, A.; Simmaco, M. (FEBS Lett., 1991)

(untitled) - Huang, C.-J.; Pauwelyn, E.; Ongena, M.; Debois, D.; Leclère, V.; Jacques, P.; Bleyaert, P.; Höfte, M. (Mol. Plant-Microbe Interact., 2015)

(untitled) - Marfey, P. (Carlsberg Res. Commun., 1984)

NMR of Proteins and Nucleic Acids - Wüthrich, K. (John Wiley & Sons, Inc., 1986)

NMR in biological research: peptides and proteins - Wüthrich, K. (North-Holland, American Elsevier, Inc., 1976)

Spectroscopic Methods for Determining Protein Structure in Solution - Gronen, A. M.; Clore, G. M. (Chapter 9, 1996)

(untitled) - Emanuele, M. C.; Scaloni, A.; Lavermicocca, P.; Jacobellis, N. S.; Camoni, L.; Di Giorgio, D.; Pucci, P.; Paci, M.; Segre, A.; Ballio, A. (FEBS Lett., 1998)

(untitled) - Ballio, A.; Bossa, F.; Camoni, L.; Di Giorgio, D.; Flamand, M.-C.; Maraite, H.; Nitti, G.; Pucci, P.; Scaloni, A. (FEBS Lett., 1996)

(untitled) - Nutkins, J. C.; Mortishire-Smith, R. J.; Packman, L. C.; Brodey, C. L.; Rainey, P. B.; Johnstone, K.; Williams, D. H. (J. Am. Chem. Soc., 1991)

(untitled) - Bassarello, C.; Lazzaroni, S.; Bifulco, G.; Lo Cantore, P.; Iacobellis, N. S.; Riccio, R.; Gomez-Paloma, L.; Evidente, A. (J. Nat. Prod., 2004)